Assessing the Influence of Familial Paternalism on Child Neglect Sentencing Decisions - Pierce, Mari B. (American journal of criminal justice, 2011)
Familial responsibilities have been found to significantly reduce the severity of sentencing outcomes of defendants in the criminal court. Additional research also has suggested that this leniency might be contingent on the type of offense, with defendants who commit crimes which imply that they are unfit parents (e.g., drug offenses) not receiving a significant reduction in their likelihood of incarceration. Utilizing familial paternalism as the theoretical basis, the current study examines whether having children influences the sentences of defendants charged with forms of criminal child neglect. The findings indicate that having children does result in significantly reduced odds of incarceration for defendants charged with child neglect. These findings support the arguments set forth by familial paternalism. However, they do not support the inference that defendants convicted of child neglect are presumed to be unfit parents. Implication of these results and directions for future research are discussed.